Effect of cyclodextrin on the quality of blueberry fruits (Vaccinium corymbosum L.) cv. Biloxi - Roncancio-Chaparro, Richard Alexander; Álvarez-Herrera, Javier Giovanni; Molano-Díaz, Julián Mauricio (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2022)
Blueberries production has increased in Colombia due to the environmental conditions that facilitate their production, especially in areas of altitude greater than 2,000 m. Blueberry fruits are highly perishable and many producing companies do not have refrigeration systems, so the application of products to increase their conservation at room temperature is necessary. The postharvest behavior of blueberry fruits was evaluated with the application of different doses of cyclodextrin (CyDs) (0, 200, 400, 600, 800 or 1,000 µg L-1). The control fruits reached 13 days after harvest (dah), while the applications of 200, 400 and 600 µg L-1 maintained consumption quality for 15 days. The dose of 400 µg L-1 of CyDs showed the best performance in parameters such as mass loss (ML), firmness, total soluble solids (TSS), maturity ratio (RM) and respiratory intensity with respect to the control, while the application of 600 µg L-1 had the highest values of pH, total anthocyanins (AnT), luminosity (L*), chromaticity and hue. The AnT increased up to 13 dah in blueberry fruits, and thereafter, they decreased, indicating senescence and loss of nutritional value. During the storage of blueberry fruits, the values of L* decreased while chromaticity from green to red (a*) increased. The application of CyDs did not affect the organoleptic properties of the treated fruits in relation to the control, therefore, the CyDs do not affect the quality of consumption.